2001
DOI: 10.1038/35084067
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and recent origin of species richness in the Cape flora of South Africa

Abstract: The Cape flora of South Africa grows in a continental area with many diverse and endemic species. We need to understand the evolutionary origins and ages of such 'hotspots' to conserve them effectively. In volcanic islands the timing of diversification can be precisely measured with potassium-argon dating. In contrast, the history of these continental species is based upon an incomplete fossil record and relatively imprecise isotopic palaeotemperature signatures. Here we use molecular phylogenetics and precise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
183
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(198 citation statements)
references
References 13 publications
11
183
1
2
Order By: Relevance
“…Using the older age estimate of 1.93 Myr for the Andean node yields a more conservative estimate of 1.93-2.78 species per Myr. However, even this minimum estimate exceeds reported species diversification rates for plants either on islands (10,23) or continents (4,6,11,26), providing the most spectacular example of explosive species diversification in plants documented to date. Low sequence divergence, lack of resolution and support, and͞or sparse taxon sampling in phylogenetic studies of other highelevation Andean plant groups (20,21,27,28) (21).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Using the older age estimate of 1.93 Myr for the Andean node yields a more conservative estimate of 1.93-2.78 species per Myr. However, even this minimum estimate exceeds reported species diversification rates for plants either on islands (10,23) or continents (4,6,11,26), providing the most spectacular example of explosive species diversification in plants documented to date. Low sequence divergence, lack of resolution and support, and͞or sparse taxon sampling in phylogenetic studies of other highelevation Andean plant groups (20,21,27,28) (21).…”
Section: Resultsmentioning
confidence: 58%
“…For plants, the idea that island-type diversifications are faster than mainland radiations has been hotly debated without conclusion (4,6,10,11,23,26). The exceptional rates of diversification found for high-elevation Andean plants suggest that island-like diversification driven by ecological opportunity may indeed outpace mainland-type radiations.…”
Section: Resultsmentioning
confidence: 99%
“…The phylogeny of this genus is still unknown, so the place of origin of Sebaea can not be suggested yet. Examples showed that the species richness in the Cape flora probably resulted from rapid and recent (7-8 MY) diversification (Cowling and Pressey, 2001;Richardson et al, 2001b). This might also be the case for Sebaea.…”
Section: Biogeographical Implicationsmentioning
confidence: 96%
“…A major component of this species turnover is replacement of individual species by closely related, ecologically similar species (Linder 1985;Linder et al 2006;Rebelo 2006;Richardson et al 2001). Many such groups of closely related, allopatric species are found in the region's most diverse lineages, including the Proteaceae, Restionaceae, and Ericaceae (Linder 2003(Linder , 2005Rebelo 2001).…”
Section: Introductionmentioning
confidence: 99%